Screening, Diversity, and Characterization of Fungal Endophytes Isolated From the Halophyte Limonium axillare and the Potential of Biocontrol Antagonists Against Fusarium oxysporum - Fedae Alhaddad; Mohammed Abu‐Dieyeh; Samir Jaoua; Mohammad A. Al‐Ghouti; Roda Al‐Thani; Talaat Ahmed (Plant Direct)
ABSTRACT Halophytes, plants that thrive in high‐salinity environments, host unique microbial communities, including fungal endophytes, which contribute to plant growth and pathogen resistance. This study aimed to isolate, identify, and evaluate the antagonistic potential of fungal endophytes from the halophytic plant Limonium axillare, collected from both inland and coastal habitats. Fungal endophytes were isolated, identified via molecular techniques, and tested for antagonistic activity against phytopathogenic fungi using dual‐culture assays. The results showed a diverse range of fungal endophytes, with Aspergillus and Cladosporium being the dominant genera. A total of 152 endophytic fungi were isolated from both locations, with 95 isolates coming from coastal plants and 57 from inland species. The isolates exhibited varying degrees of antagonistic activity against phytopathogens, highlighting their potential role in plant protection. Further research is needed to clarify these interactions' mechanisms and investigate their practical applications in agriculture. An endophytic isolate of Aspergillus terreus strain ((AL10) lim10qu) (ON210104.1) exhibited potent in vitro antifungal activity against Fusarium oxysporum, a pathogenic fungus affecting tomato plants. Greenhouse experiments demonstrated that the fungus significantly increased both the length of tomato seedlings and the overall plant biomass. Both laboratory‐based (in vitro) and field‐based (in vivo) evaluations of the strain ((AL10) lim10qu) (A. terreus) against F. oxysporum suggest the promising role of endophytes as effective biological control agents. Analysis using Gas Chromatography–Mass Spectrometry of the fungal extract detected around 100 compounds (secondary metabolites). In addition to gradually reducing the need for chemical fungicides, bio‐products can also contribute to sustainable agriculture.